2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of affective state estimations using an on-line reporting device during human-robot interactions

Abstract: Abstract-In order to develop a friendly and safe interaction between humans and robots, it is essential for the robot to evaluate user's affective states and respond accordingly. However, affective states are typically assessed using offline questionnaires and user reports. In this paper we investigate the use of an online-device for collecting real-time user reports of affective state during interaction with a robot. These reports are compared to both previous survey reports taken after the interaction, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Several researchers have employed GSR to characterize people's responses during HRI or to enable a robot to respond to a human's affective state [21,28,35,39,45].…”
Section: Galvanic Skin Response (Gsr)mentioning
confidence: 99%
“…Several researchers have employed GSR to characterize people's responses during HRI or to enable a robot to respond to a human's affective state [21,28,35,39,45].…”
Section: Galvanic Skin Response (Gsr)mentioning
confidence: 99%
“…The last category includes devices aimed at providing direct feedback during the experiment: these, as for questionnaires, provide a subjective measure of perceived safety, which however can be acquired in "real-time" rather than at the end of the experiment. The first device, used by Zoghbi et al in [25], was named Affective-State Reporting Device (ASRD), and was "an in-house developed modified joystick [...] to record affective states expressed by each user" [25]. The second, used by Koay and coauthors in [46,47,49,73,77] was the so-called Comfort Level Device (CLD), i.e., "a handheld comfort level monitoring device that would allow subjects to indicate their internal comfort level during the experiment" [46].…”
Section: Direct Input Devicesmentioning
confidence: 99%
“…Industrial manipulators constitute the type of robot on which the largest number of papers were written on perceived safety in pHRI. Earlier works used standard industrial manipulators, and precisely CRS A460 [20,21,[23][24][25], Mitsubishi Movemaster RM-501 [18,19,22], ABB IRB-120 [29,31], Comau SMART SiX [27], Yaskawa MOTOMAN-K10S and SONY SRX-410 [28]. More recent papers, instead, started using collaborative robots: KUKA LBR iiwa [35,38,43], Kinova MICO [33], UR3 [44], UR5 [39], UR10, [30], Sawyer [45], and Franka Emika Panda [42].…”
Section: Overview On Industrial Manipulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the basis of many sensor techniques, including electrodermal response, psychogalvanic reflex, skin conductance response, and skin conductance level (Conesa, 1995). Studies have found that skin response is positively correlated with body arousal (Meisner, Isler, & Trinkle, 2008;Swangnetr, Zhu, Kaber, & Taylor, 2010;Zoghbi, Croft, Kulic, & Van der Loos, 2009;Rosenthal-von, Krämer, Hoffmann, Sobieraj, & Eimler, 2013;Chen, King, Thomaz, & Kemp, 2014). For instance, Bradley and Lang (2000) found a significant correlation between emotional stimuli and skin conductance.…”
Section: Characterizing Human Emotionmentioning
confidence: 99%